Successful TAVI-in-TAVI for degenerated bioprosthetic aortic valve with severe stenosis-a case report - Apostu Alexandra; Deleanu Dan; Parasca Cătălina; Capșa Răzvan; Dobrovie Monica; Popescu Bogdan Alexandru; Chioncel Ovidiu; Iliescu Vlad Anton; Jurcuţ Ruxandra (Sciendo, 2024)
Aortic stenosis is one of the leading causes of valvular disease requiring surgery or transcatheter intervention, with a rising prevalence due to the aging population. Current guidelines recommend transcatheter aortic valve implantation (TAVI) as the first-line treatment for patients with symptomatic severe aortic stenosis and high surgical risk. The indications for TAVI have expanded to low-surgical-risk patients due to increased operator experience and improved implanted devices with a dramatic reduction of complications. Considering the limited durability of bioprostheses, TAVI-in-TAVI procedures have been successfully performed as an alternative to surgery.